FORMATION OF LEGAL COMPETENCE BASED ON LINE INTERACTION OF PARTICIPANTS OF THE EDUCATIONAL PROCESS - Rzhevskaya Nataliіa (Continuing Professional Education: Theory and Practice, 2019)
Investigated the pedagogical problem of formation of legal competence through online interaction of participants of the educational process. The author emphasized that one of the pressing problems is the technology gap in education, outdated forms and form of educational information that leads, of course, to reduce the effectiveness of training.Also problematic is the question of correct and full use of information technology opportunities, not just playing classical forms and methods of training in information content.Emphasized that the online interaction between the participants of the educational process is not limited to the concept of gamification, it is wider and is improving the user experience in software products. The framework of legal expertise that incorporates the following components: axiological, cognitive, empirical, humanistic, acmeological. Placed distribution the methods within educational technologies based on modern technological innovations and online interaction between participants of the educational process for the constituent components of legal competence. Thus, formation of axiological component of legal competence presented using blogs, social networks, work with electrons books; forming cognitive component of legal competence submitted using the chat forum; forming component of empirical legal competence - the creation of e-encyclopedias; forming humanistic component - the massive online courses; acmeological forming component - web quest. Emphasized that the use of educational technologies based on modern technological progress contributes to the preparation of individual skills and attitudes formed about the level of scientific progress and its opportunities of ita using. It is concluded that the development, implementation in the educational process of modern technologies and their integration with classical methods, the use of social media services helps motivated learning when the student is able to search for information and interest alone. This makes it possible to increase the quality of training of future professionals capable of adequately represent the Ukrainian education in Europe. Proved that the harmonious use of modern technological equipment in the formation of legal competence in terms of its components, the components will shock not only to rethink teaching methods, but is practically significant for teachers.